DINAMIKA KEBIJAKAN PUBLIK DALAM PENGELOLAAN ASET DANAU LIMBOTO DI KABUPATEN GORONTALO - Trisusanti Lamangida (JPPE : Jurnal Perencanaan & Pengembangan Ekonomi, 2019)
The dynamics of public policy in managing the assets of the Limboto lake area in Gorontalo Regency is the focus of this research. This article aims to analyze and explain the dynamics of public policy management of the Lake Limboto area assets. The method and approach used is descriptive qualitative. Data collection was done by purposive sampling technique (Sugiyono: 2010), observation, interviews and documentation. Data analysis was carried out following an "interactive model" (Miles Huberman & Saldana: 2014), namely: data collection, data display, data condensation, conclusions / drawing. The findings indicate that the public policy on the management of the Limboto lake area assets is not optimal. The Central Government at the National Lake Indonesia Conference, through the 2009 Bali agreement, involving 9 State Ministries of the Republic of Indonesia, has set 15 lake priorities that will be handled together in an integrated and sustainable manner for the period 2010-2014 including Limboto Lake. Previous Regional Regulation No. 4 of 2004, Regional Regulation No. 5, and PERDA No. 1 of 2008 concerning the management of Lake Limboto, Provincial Government Regulation No. 4 of 2011, but all of these policy products have not been able to overcome the problem of siltation of lakes. The dynamics of Limboto lake management public policy involving 20 stakeholders (Hasim; 2012) still have high influence and interests. The choice of the paradigm of the right management of Lake Limboto's public policy is oriented to the economic growth of the community, according to the perspective of public entrepreneurship (Syam; Lamangida; 2018), which has implications for increasing regional investment value added (NTID) and PAD (Lamangida, 2018), contributing to Local Government in building participation, the independence of the community, especially the people living along the watershed, upstream, and on the shores of Lake Limboto Keywords:Policy, Public, Management, Good Governance, NTID and PAD